Lactobacillus endocarditis: A case report in France and literature review. (2020) - Campagne, J.; Guichard, J.F.; Moulhade, M.C.; Kawski, H.; Maurier, F.
Abstract: Lactobacilli are commensal bacteria in the normal flora of the oral cavity, gastrointestinal and genital tract. However, few cases of lactobacilli-induced bacteremia or endocarditis have been reported, particularly in immunocompromised patients. We reported a rare case of a 57-year-old man with a Lactobacillus rhamnosus endocarditis without immunodeficiency in his medical history. He received a dental scaling one year before. Clinical presentation included weight loss, heart murmur, ankle arthritis and splinter hemorrhage. Echocardiography showed a mitral prolapse and a 16 mm vegetation associated with a valvular perforation. All blood cultures were positive for Lactobacillus rhamnosus . Antibacterial regimen with amoxicillin and gentamicin led to recovery without surgery. We present a literature review of the lactobacillary endocarditis cases published since 1992. Valvulopathy, dental or invasive procedures and probiotics use were the main underlying conditions, in contrary to immunodeficiency. Diagnosis of lactobacillary endocarditis should be more considered and a treatment with penicillin and aminoglycoside should be promptly introduced in life-threatening cases.